Parents' Hesitancy to Vaccinate Their Children Against COVID-19, a Country-Wide Survey - Alhazza, Sultan F.; Altalhi, Ali M.; Alamri, Khaled M.; Alenazi, Saleh S.; Alqarni, Bader A.; Almohaya, Abdulellah M. (Frontiers in Public Health, 2022)
Objective: Parents' hesitancy (PH) toward childhood vaccination, including the vaccine of coronavirus disease (COVID-19), is one of the top public health threats. We aim to assess the PH toward children COVID-19 vaccination as compared to PH toward children routine vaccination among the residents of Saudi Arabia. Method: Before the official approval of children's COVID-19 vaccination in the country, a cross-sectional study using an electronically distributed survey was performed. Responses from parents of children younger than 18 years of age were accepted. The Oxford COVID-19 vaccine hesitancy scale (OC19-VHS) and the routine vaccination hesitancy scale (R-VHS) were used. Parents were classified as hesitant, non-hesitant, and unsure. Results: Between June 18th-30th, 2021, we included 1,052 parents. More than half of the parents were positive toward the childhood COVID-19 vaccination (63%) while 10% were unsure. Higher parental hesitancy toward children COVID-19 vaccination among mothers, parents younger than 40 years, did not receive COVID-19 nor influenza vaccines, had higher educational levels, and parents who recovered from COVID-19 infection. Hesitancy was mainly driven by the novelty of the vaccines and the fear of serious adverse effects. Compared to the routine vaccination, parents were more hesitant toward COVID-19 vaccination (6% vs. 27%). Conclusion: Generally, parents in Saudi Arabia were positive toward children's COVID-19 vaccination. Focused education to reassure hesitant parents on the safety of the vaccine is essential to achieve larger vaccination coverage.